Stylistic Markers Of Authenticity In Ḥadīth Texts: An Integrative Framework Bridging ʿilm Al-Ḥadīth And Literary Stylistics - Hishomudin Ahmad; Norfarhana Ahmad Ghafar (Universiti Sains Islam Malaysia, 2026)
Journal of Hadith Studies, Volume 10 Issue 2 Page (39–50)